Alle origini del pensiero simbolico: una prospettiva filogenetica - Adornetti, Ines (Rivista Italiana di Filosofia del Linguaggio, 2014)
This article discusses two theoretical models proposed to explain the origins of symbolic thought in cognitive archeology and paleoanthropology: the model of explosion (also called the model of Upper Paleolithic revolution) and the gradualist model. According to the first model, symbolic thought is unique to Homo sapiens and has emerged suddenly and recently in human phylogenesis through a process of cultural evolution. According to the gradualist model, symbolic thought is the product of biological evolution and is present in species other than Homo sapiens. The article shows some epistemological and empirical problems of the model of the explosion and, on the basis of these critical issues, supports the validity of the gradualist model.